PENGEMBANGAN BAHAN AJAR TEMATIK TERINTEGRASI NILAI-NILAI ISLAM DAN SAINS UNTUK MENINGKTAKAN KARAKTER RELIGIUS SISWA - Fenti Nurjanah; Retno Triwoelandari; M. Kholil Nawawi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2018)
ABSTRACT The decline in the character of the nation's children is a form of failure in the process of implementing education. This is proven, that the mandate of Law No. 20 of 2003 Article 3 and character values ​​as a national culture that must be developed in accordance with the Ministry of National Education (Ministry of National Education) are not implemented. Then it needs a real effort to integrate Islamic values ​​on subjects. Integration of Islamic values ​​can be carried out on various subjects, one of which is science. Given the purpose of science, among others, is to increase human piety towards the greatness of God, as well as increase human awareness to respect nature as one of God's creations. The manifestation of integration is by compiling teaching materials in the form of modules to support the learning process in schools in order to improve the religious character of students. The purpose of this study was to determine the procedure for preparing modules as a tool in improving the religious character of students, knowing the feasibility level of teaching materials in the form of modules, and knowing the increase in religious character that occurred in students after learning to use the module. This study uses the Research and Development (R & D) method which was modified by Nana Syaodih Sukmadinata into three stages, namely the introduction, development, and testing stages. at the development stage, the results of the study showed a number of material experts 96.25%, design experts 80.88% and linguists 67.85%. At the testing stage, the results are 95.39% for the limited test, namely in the 5-C class and the broad test 1 in the 5-A class is 95.85% and 88.80% in the broad test II, namely class 5-B. The final test results show sig. 0.00 <0.05 with differences in the results in the experimental class 56,337 and the control class 52,959 which is 3,378 larger experimental classes. Thus, the development of modules as effective teaching materials is used to improve the religious character of students based on the preparation process and the level of feasibility. ABSTRAK Merosotnya karakter anak bangsa merupakan bentuk kegagalan dalam proses pelaksanaan pendidikan. Hal ini dibuktikan, bahwa amanah UU No. 20 Tahun 2003 Pasal 3 dan nilai karakter sebagai budaya bangsa yang harus dikembangkan sesuai Kemendiknas (Kementerian Pendidikan Nasional) tidak terlaksana. Maka perlu usaha nyata untuk melakukan integrasi nilai-nilai Islam pada mata pelajaran. Integrasi nilai-nilai Islam dapat dilakukan pada berbagai mata pelajaran, salah satunya adalah sains. Mengingat tujuan sains antara lain adalah untuk meningkatkan ketakwaan manusia terhadap kebesaran Tuhan, serta meningkatkan kesadaran manusia untuk menghargai alam sebagai salah satu ciptaan Tuhan. Wujud dari pengintegrasian tersebut yaitu dengan menyusun bahan ajar berupa modul untuk menunjang proses pembelajaran di sekolah dalam rangka meningkatkan karakter religius siswa. Tujuan penelitian ini adalah untuk mengetahui prosedur penyusunan modul sebagai alat dalam meningkatkan karakter religius siswa, mengetahui tingkat kelayakan bahan ajar berupa modul, dan mengetahui peningkatan karakter religius yang terjadi pada siswa setelah belajar menggunakan modul. Penelitian ini menggunakan metode Research and Development (R & D) yang dimodifikasi oleh Nana Syaodih Sukmadinata menjadi tiga tahap yaitu tahap pendahuluan, pengembangan, dan pengujian. pada tahap pengembangan, hasil penelitian menunjukkan angka angka ahli materi 96.25%, ahli desain 80.88% dan ahli bahasa 67.85%. Pada tahap pengujian, hasilnya yaitu 95.39% untuk uji terbatas yaitu pada kelas 5-C dan uji luas 1 pada kelas 5-A hasilnya 95.85% serta 88.80% pada uji luas II yaitu kelas 5-B. Hasil akhir pengujian menunjukkan sig. 0.00 < 0.05 dengan perbedaan hasil pada kelas eksperimen 56.337 dan kelas kontrol 52.959 yaitu 3.378 lebih besar kelas eksperimen. Dengan demikian, pengembangan modul sebagai bahan ajar efektif digunakan untuk meningkatkan karakter religius siswa berdasarkan proses penyusunan dan tingkat kelayakannya.